Analisis Tingkat Kepatuhan Bendahara Pemerintah Kabupaten Soppeng Dalam Penyetoran Pajak - Nur Fadli; Andi Zulfayani (AkMen JURNAL ILMIAH, 2021)
The contribution of taxes to development in Indonesia is very significant to support the government activity. Tax collection involves local government treasurers to carry out calculations to tax reporting. This study aimed to analyze the compliance of the government treasurer in terms of understanding the self-assessment system, service quality, education level, and tax sanctions. Determination of respondents using purposive sampling technique with the criteria that employees that acts as treasurer. The research method applies quantitative research using multiple linear regression models to test the proposed hypothesis(α= 5% : 0.05). The results of the t-test indicate that there is an effect of understanding, education level, and tax sanctions on taxpayer compliance partially (tcount> ttable; p<0.05) while Service Quality has no effect (p>0.05). The results of the F-test indicate that the independent variables have a simultaneous effect (Fcount>Ftable; p<0.05) on Taxpayer Compliance with an accuracy of 66.8% while the rest is influenced by other factors not studied. Government treasurers who understand their duties and are supported by quality tax service services and know the consequences of violations in carrying out their duties will facilitate the implementation of their tax obligations and increase their compliance as taxpayers.